Changes in long jump take-off technique with increasing run-up speed - Bridgett, L. A.; Linthorne, N. P. (Journal of Sports Sciences, 2006)
The aim of this study was to determine the influence of run-up speed on take-off technique in the long jump. Seventy-one jumps by an elite male long jumper were recorded in the sagittal plane by a high-speed video camera. A wide range of run-up speeds was obtained using direct intervention to set the length of the athlete's run-up. As the athlete's run-up speed increased, the jump distance and take-off speed increased, the leg angle at touchdown remained almost unchanged, and the take-off angle and take-off duration steadily decreased. The predictions of two previously published mathematical models of the long jump take-off are in reasonable agreement with the experimental data.